Pengembangan Media Komik Strip (Komstrip) dalam Meningkatkan Kemampuan Membaca Pemahaman pada Pelajaran Bahasa Indonesia Kelas V SD 2 Daren Jepara - Farid Aulal Khuluqi; Muhammad Misbahul Munir (Universitas Ngudi Waluyo, 2026)
This study aims to develop comic strip-based learning media (Komstrip) as an innovative tool in improving the reading comprehension skills of fifth-grade students at SD 2 Daren Jepara. The background of this study is based on the low interest in reading and students' difficulties in understanding reading texts in Indonesian language lessons. The research method used is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The research instruments are validation sheets from media experts and material experts, as well as student reading comprehension tests. The results show that the Komstrip media obtained the